2018
DOI: 10.18552/ijpblhsc.v6i2.493
|View full text |Cite
|
Sign up to set email alerts
|

Developing Measures of Placement Quality in Allied Health, Dentistry, Medicine, and Pharmacy

Abstract: As placement numbers expand, there is a concern that the quality of student experience and learning may diminish. Furthermore, there is a paucity of evidence for evaluation and quality improvement in clinical health placements and there have been few studies undertaken to assess quality. Valid and reliable measures of placement quality are needed to provide an evidence-base to guide decisions about the most efficient and effective placement models in health. A two-phase mixed methods design, using a modified D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…Firstly, an Exploratory Factor Analysis (EFA) was conducted to duplicate the methods used in the McAllister article (McAllister et al, 2018) to assess the degree to which the seven items in the PQS sufficiently explained the underlying construct of rural clinical placements. The Bartlett's Test of Sphericity (SAS Institute, 2020) was used to determine whether the data were suitable for factor analyses.…”
Section: Validitymentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, an Exploratory Factor Analysis (EFA) was conducted to duplicate the methods used in the McAllister article (McAllister et al, 2018) to assess the degree to which the seven items in the PQS sufficiently explained the underlying construct of rural clinical placements. The Bartlett's Test of Sphericity (SAS Institute, 2020) was used to determine whether the data were suitable for factor analyses.…”
Section: Validitymentioning
confidence: 99%
“…The authors found broad agreement on the elements that measure the quality of clinical placements amongst dentistry, medicine and pharmacy students. The tool was valid and reliable with EFA showing one component accounting for 58.5% of the variance of survey data (McAllister et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations